PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA KARYAWAN PT. PUSAKA MEGAH BUMI NUSANTARA PELALAWAN - M. Fauzi Indrawan; Okta Karneli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Human resources is one component that has an important role in achieving the goals of a company, including the existing human resources at PT. Pusaka Megah Bumi Nusantara Pelalawan Archipelago. The object of this research is PT. Pusaka Megah Bumi Nusantara Pelalawan Archipelago. This study aims to determine how much influence the work environment and work motivation have on employee job satisfaction at PT. Pusaka Megah Bumi Nusantara Pelalawan Archipelago. The research method uses quantitative data collection through questionnaires and interviews. The focus of sampling in this study were 79 employees of PT. Pusaka Megah Bumi Nusantara Pelalawan using purposive sampling technique method. The data analysis technique used is simple linear regression analysis and multiple linear regression analysis using SPSS 25. Based on the results of the research hypothesis test, it shows that there is a partially significant effect between work environment on job satisfaction with tcount 5.487 > ttabel 1.991, work motivation on job satisfaction. with a value of 5,605 > ttabel 1,991. In this study, the strongest contribution to job satisfaction was the work motivation variable with an R square value of 0.290. Furthermore, it is also proven that there is a simultaneous influence between Work Environment and Work Motivation on Job Satisfaction of Employees of PT. Pusaka Megah Bumi Nusantara Pelalawan Archipelago. with the value of Fcount 20,842 > from Ftabel of 3.12. Overall, the results of the simple and multiple regression tests were well received. Next for PT. Pusaka Megah Bumi Nusantara Pelalawan is advised to pay attention to the work environment and work motivation so that employee job satisfaction will increase every year, and for further research to provide the latest theories to increase knowledge and strengthen the results of research. Keywords: Work Environment and Work Motivation, and Job Satisfaction.